Assessment of Lipid Profile and Cytokine (IL-13, TGF-β) with sICAM-1in Patients Infected with Intestinal Parasite (Entamoeba histolytica, Giardia lamblia and Blastocystis hominis) - Esra I. Wahid-Aldeen (Journal of Global Pharma Technology, 2016)
Tests were assessed in sera of 150 patients infected with intestinal parasites of E.histolytica (50 case), Giardia lamblia (50 case) and Blastocystis hominis (50 case), as well as 20 apparently healthy controls whom attended to Children Hospital , Kirkuk General Hospital And Azadi teaching Hospital in Kirkuk city-Iraq, from February- August 2017. Biochemical parameters include a lipid profile, while immunological parameters include serum level of IL-13, TGF-β and soluble intracellular adhesion molecule-1) sICAM-1 (. Biochemical parameters showed a significant correlation between low serum lipid levels in infected intestinal parasites especially in the level of cholesterol was significantly decreased in patients infected with G.lamblia (107.36 ± 10.82 mg/dl) and E.histolytica(110.88 ± 9.45 mg/dl) compared to control group and patients infected with B.hominis (P ≤ 0.05) . The level of T.G. and VLDL also showed significantly decreased in patients infected with E.histolytica(57.52 ±8.73 mg/dl) compared to control and patients infected with B.hominis, while all patients showed a significant decrease in HDL level. Serum level of IL-13 and sICAM-1were significantly increased in all patients infected with intestinal parasite, while there was a significantly increased serum level of TGF-β in patients infected with B.hominis and E.histolytica, the current study conclude that intestinal parasite work to consumed fat from the host because it cannot synthesize it by itself , and this result suggest a role of IL-13 pathogenesis of intestinal parasitic infection ,also the increase in the level of TGF-β and sICAM-1 in B.hominis patient may suggest that TGF-β causes increased expression of endothelial ICAM-1and neutrophil-mediated intestinal injury.Keywords: Entamobea histolytica, Giardia lamblia, Blastocystis hominis, sICAM-1, IL-13, TGF-β, Lipid Profile.